Detection and phylogenetic analyses of spike genes in porcine epidemic diarrhea virus strains circulating in China in 2016–2017 - Zhang, Qiaoling (Virol J, 2017)
BACKGROUND: Large-scale outbreaks of porcine epidemic diarrhea (PED) have re-emerged in China in recent years. However, little is known about the genetic diversity and molecular epidemiology of field strains of PED virus (PEDV) in China in 2016–2017. To address this issue, in this study, 116 diarrhea samples were collected from pig farms in 6 Chinese provinces in 2016–2017 and were detected using PCR for main porcine enteric pathogens, including PEDV, porcine deltacoronavirus (PDCoV), porcine transmissible gastroenteritis virus (TGEV) and porcine kobuvirus (PKV). In addition, the complete S genes from 11 representative PEDV strains were sequenced and analyzed. RESULTS: PCR detection showed that 52.6% (61/116) of these samples were positive for PEDV. Furthermore, sequencing results for the spike (S) genes from 11 of the epidemic PEDV strains showed 93–94% nucleotide identity and 92–93% amino acid identity with the classical CV777 strain. Compared with the CV777 vaccine strain, these strains had an insertion (A(133)), a deletion (G(155)), and a continuous 4-amino-acid insertion ((56)NNTN(59)) in the S1 region. Phylogenetic analysis based on the S gene indicated that the 11 assessed PEDV strains were genetically diverse and clustered into the G2 group. These results demonstrate that the epidemic strains of PEDV in China in 2016–2017 are mainly virulent strains that belong to the G2 group and genetically differ from the vaccine strain. Importantly, this is the first report that the samples collected in Hainan Province were positive for PEDV (59.2%, 25/42). CONCLUSIONS: To our knowledge, this article presents the first report of a virulent PEDV strain isolated from Hainan Island, China. The results of this study will contribute to the understanding of the epidemiology and genetic characteristics of PEDV in China.